Hubungan Intensitas Latihan Musik Gamelan Bali dan Kecerdasan Emosional - Ariani, Nyoman Wiraadi Tria; Suarya, Luh Made Karisma Sukmayanti (Jurnal Psikologi Udayana, 2013)
Nowdays, more teenagers have a tendency of experiencing emotional difficulties that needed a way to overcome them, such as by developing the adolescent's emotional intelligence. The development of adolescent's emotional intelligence can be done through music, one of them with the traditional Indonesian gamelan music of Bali. Exercise at Balinese gamelan is played by a group of individuals together with the rules or certain grip. At the time of practicing gamelan, besides having a duty to beat his own gamelan instrument, the individual must also consider the gamelan instruments played by colleagues in the ensemble, so can produce a harmonious sound of gamelan (Donder, 2005). This study aims to determine the relationship between exercise intensity Balinese gamelan music and emotional intelligence.   This study uses quantitative correlation with the number of subjects 135 students of ISI Denpasar. The sampling method used purposive sampling and data collection tool using Exercise Intensity Scale Gamelan Music of Bali (r = 0.848) and Emotional Intelligence Scale (r = 0.772). Methods of data analysis using Product-Moment correlation, which then obtained yield was 0,550. The results showed a positive relationship between exercise intensity of Balinese gamelan music and emotional intelligence are the higher intensity of exercise at Balinese gamelan music, the higher the emotional intelligence will be. Intensity exercise Balinese gamelan music's variable can contribute 30,25% to the variables of emotional intelligence, while 69.75% was influenced by other factors than the variable of intensity exercise Balinese gamelan music. Other factors beyond the intensity exercise Balinese gamelan music's variable by Goleman (1997) is a family environment, environmental non-family, physical, and psychological.   Keywords: Intensity of exercise to music, Balinese gamelan, emotional intelligence